Contemporary issues in couples counseling : a choice theory and reality therapy approach - Robey, Patricia A.; Wubbolding, Robert E.; Carlson, Jon. (New York : Routledge, 2012)
'Contemporary Issues in Couples Counseling addresses the most common and difficult issues that people in the helping professions face when using CBT with couples--and provides concrete solutions for addressing them effectively. In it, clinicians will find a handy reference for professionals who are looking for useful information and skills that can be applied immediately in their sessions. The book uses the time-tested, evidence-based strategies for helping clients focus on the here and now, not the past, and for helping clinicians create effective treatment plans and ensure that that clients meet their individual needs while also addressing the needs of their partners'--
Includes bibliographical references and index.
Keywords: Couples -- Counseling of; Reality therapy; Control theory